Exploring the impact of polychlorinated biphenyls on comorbidity and potential mitigation strategies - Ying Gao; Ying Gao; Han Lu; Huan Zhou; Jiaxing Tan; Jiaxing Tan (Frontiers Media S.A., 2024)
IntroductionPolychlorinated Biphenyls (PCBs) persist in the environment and accumulate in humans. Currently, there is a lack of understanding about the overall impact of PCBs on human health, and effective interventions for exposed populations are insufficient.MethodsOur study aimed to assess the impact of PCBs on various diseases and mortality risks using data from the National Health and Nutrition Examination Survey, while proposing lifestyle adjustments, particularly dietary modifications, to mitigate mortality risk. Statistical analyses employed principal component analysis, multifactorial logistic regression, multifactorial Cox regression, comorbidity network analysis, and machine learning prediction models.ResultsResults indicated significant associations between 7 types of PCBs and 12 diseases (p < 0.05), with 6 diseases showing significant positive correlations (OR > 1, p < 0.05), along with listing the 25 most relevant diseases, such as asthma and chronic bronchitis (OR [95% CI] = 5.85 [4.37, 7.83], p < 0.0001), arthritis and osteoporosis (OR [95% CI] = 6.27 [5.23, 7.55], p < 0.0001). This suggested that PCBs may be intimately involved in the development and progression of multiple diseases. By constructing multidimensional machine learning models and conducting multiple iterations for precision and error measurement, PCBs may have the potential to become specific biomarkers for certain diseases in the future. Building upon this, we further suggested that controlling dietary intake to reduce dietary inflammatory index (DII) could lower mortality and disease risks.DiscussionWhile PCBs were independent risk factors for mortality, substantial evidence suggested that adjusting DII might mitigate the adverse effects of PCBs to some extent. Further physiological mechanisms require deeper exploration through additional research.